EVALUATION DES CONNAISSANCES SUR LE LAVAGE DES MAINS CHEZ LES ELEVES DES ECOLES PRIMAIRES DE LA SOUS DIVISION EDUCATIONNELLE DE KALIMA 2021-2022 - Bernoulli, AMURI LUKAMBA; Alexis, KABANGE NUMBI; Laurent, OMARI MASUDI (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2025)
The research carried out in the educational sub-division of Kalima on the assessment of the level of knowledge of primary school students on hand washing leads to the following:The overall level of hand washing was good, 6 out of 10 students (65.4)97 were educated on how to wash hands; 76.8 from home and 71.0 by parents Most people know that dirty hands transmit diseases (86.7).Handwashing helps students prevent diseases from dirty hands so they can stay healthy.